PENGARUH MODEL PEMBELAJARAN RECIPROCAL TEACHING TERHADAP KETERAMPILAN BERBICARA SISWA KELAS V SDN 1 BAREJULAT - Yunita Aryani; Ida Bagus Kade Gunayasa; Heri Hadi Saputra (Program Studi PGSD, FKIP, Universitas Mataram, 2021)
This study aims to determine the effect of the reciprocal teaching learning model on the speaking skills of fifth graders at SDN 1 Barejulat. The results of this study are expected to be useful theoretically and practically. The type of experimental research used is Quasi Experimental Design in the category of Noneequivalent Control Group Design. Data collection techniques using observation and performance appraisal. The data analysis technique is the prerequisite test 1). Normality test 2). Homogeneity test 3). Hypothesis testing using the Anacova test. The results showed that the highest pretest score for the control class (Vb) was 70, while the lowest score was 45. Then the highest pretest result for the experimental class (Va) was 75, the lowest was 43. The highest posttest score for the control class (Vb) was 73, while the the lowest was 50. Then the highest posttest result in experimental class (Va) was 83, the lowest score was 65. This indicates that there is an effect of the reciprocal teaching learning model on the speaking skills of fifth grade students at SDN 1 Barejulat.